Evaluasi Pelaksanaan Pemberdayaan Lingkungan Permukiman Berbasis Komunitas di Kawasan Bantaran Sungai Kota Yogyakarta - Nurokhman, Nurokhman; Suharyanto, Indra; Kristiyanto, Hery; Erlina, Erlina; Subagyo, Singgih; Suryanto, Suryanto; Sukarno, Sukarno; Santoso, Fattah Setiawan; Surifah, Surifah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The banks of the Gajahwong River in Yogyakarta City are part of the slum area based on a decree from the Mayor of Yogyakarta in 2016. Various Community-Based Environmental Empowerment Programs (PLPBK) have been implemented until 2022. For this reason, it is necessary to carry out a qualitative evaluation of the success of its implementation in overcoming slums in a sustainable manner, including involvement the parties in it. The condition of the Warungboto Slum Area is a mild slum with an average sectoral slum of 23.7% in certain RTs. The existence of the Kotaku program with the handling of increasing settlements in terms of road infrastructure, drainage, infiltration wells has had an impact on the non-slum parameter score but the handling of house buildings and riverbank inspection roads is still problematic. Thus the involvement and commitment of all parties, the government, local communities as well as NGOs and universities need to be strengthened so that slum reduction can be optimally realized.